1998
DOI: 10.1007/s004380050844
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase 2A is involved in hyphal growth of Neurospora crassa

Abstract: Cantharidin and calyculin A, natural toxins that are inhibitors of protein phosphatases 1 and 2A (PPI and PP2A, respectively). inhibit Neurospora crassa hyphal growth. When N. crassa was grown in the presence of either drug, abnormalities were observed at hyphal tips. In addition, both drugs induced an increase in hyphal branching. Cantharidin inhibited N. crassa hyphal growth in a temperature-dependent manner, as the effect of the drug was more pronounced at 34 degrees C than at 25 degrees C. In addition to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Because the catalytic subunits of PP1 and PP2A (encoded for by the ppp-1 and pph-1 genes, respectively) are essential for cell survival in Neurospora and other eukaryotes (Yatzkan and Yarden 1995;Zeke et al 2003), we used repeat-induced point mutation (RIP; Cambareri et al 1989) to obtain partially functional To examine whether these mutations led to the decrease of the phosphatase activity of PP1, phosphatase assay (see supplemental materials) was performed using extracts prepared from cultures grown in LL, a condition that the clock is not running. The 32 P-labeled phosphorylase a is used as the substrate of the assay in the presence or absence of inhibitor-2, a specific protein inhibitor for PP1 (Krebs and Fischer 1962;Yatzkan et al 1998;Cohen 2002). As shown in Figure 1A, the inhibitor-2-sensitive phosphatase acitivity was significantly reduced in the ppp-1 RIP strain, indicating that the mutations resulted in a partial functional PPP-1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…Because the catalytic subunits of PP1 and PP2A (encoded for by the ppp-1 and pph-1 genes, respectively) are essential for cell survival in Neurospora and other eukaryotes (Yatzkan and Yarden 1995;Zeke et al 2003), we used repeat-induced point mutation (RIP; Cambareri et al 1989) to obtain partially functional To examine whether these mutations led to the decrease of the phosphatase activity of PP1, phosphatase assay (see supplemental materials) was performed using extracts prepared from cultures grown in LL, a condition that the clock is not running. The 32 P-labeled phosphorylase a is used as the substrate of the assay in the presence or absence of inhibitor-2, a specific protein inhibitor for PP1 (Krebs and Fischer 1962;Yatzkan et al 1998;Cohen 2002). As shown in Figure 1A, the inhibitor-2-sensitive phosphatase acitivity was significantly reduced in the ppp-1 RIP strain, indicating that the mutations resulted in a partial functional PPP-1 protein.…”
Section: Resultsmentioning
confidence: 99%
“…The antifungal spectrum and potency of cantharidin against Dfks mutants of S. cerevisiae differed from those of PLME. The appearance of balloon-like hyphae induced by PP1A and PP2A inhibitors was reported to be limited at the hyphal tips in N. crassa [15]. With PLME, expansion in diameter was observed throughout the hyphae of A. fumigatus (Fig.…”
Section: Fig 2 Effects Of Plme On Hyphal Morphology In Aspergillus Fmentioning
confidence: 90%
“…However, there have been few reports on the physiological role of PP2A in filamentous fungi [15,16]. Cantharidin, an inhibitor of PP1A and PP2A, inhibits the hyphal growth of Neurospora crassa accompanied by swollen hyphal tips and an increase in hyphal branching [15].…”
Section: Fig 2 Effects Of Plme On Hyphal Morphology In Aspergillus Fmentioning
confidence: 99%
“…Of particular interest is whether CPP1 affects other fumonisin biosynthesis regulatory genes, particularly the genes FUM21, ZFR1 and GBB1 that are positively associated with fumonisin biosynthesis (Brown et al, 2007;Flaherty & Woloshuk, 2004;Sagaram & Shim, 2007). Meanwhile, it is well recognized that type 2A protein phosphatases are associated with cell differentiation and development in eukaryotes, including filamentous fungi (Dickman & Yarden, 1999;Hunter, 1995;Mayer-Jaekel & Hemmings, 1994;Shenolikar, 1994;Yatzkan et al, 1998), and multiple PP179 phenotypes suggested that CPP1 is also involved in multiple downstream signalling pathways in F. verticillioides. Strikingly, CPP1 deletion led to a hyphal-swelling phenotype, thereby suggesting the functional role of CPP1 in morphogenesis.…”
Section: Discussionmentioning
confidence: 99%